2022
DOI: 10.1111/1467-9566.13437
|View full text |Cite
|
Sign up to set email alerts
|

Attending to child agency in paediatric palliative care consultations: Adults’ use of tag questions directed to the child

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…Moreover, participants may have differed in their conceptualization of given concepts (e.g., what an open‐ended question is, what they consider to be often) and may have conceptualized such concepts incorrectly, thereby confounding their responses. This is particularly important when considering our findings about question type, as the majority of participants reported considering the types of questions they ask children, yet other research has found that healthcare providers are susceptible to using more suggestive, option‐posing questions (i.e., tag questions 36,37 ). Finally, participants were not blinded to the purpose of the study, which may have influenced their responses to the survey.…”
Section: Limitations and Future Directionsmentioning
confidence: 98%
“…Moreover, participants may have differed in their conceptualization of given concepts (e.g., what an open‐ended question is, what they consider to be often) and may have conceptualized such concepts incorrectly, thereby confounding their responses. This is particularly important when considering our findings about question type, as the majority of participants reported considering the types of questions they ask children, yet other research has found that healthcare providers are susceptible to using more suggestive, option‐posing questions (i.e., tag questions 36,37 ). Finally, participants were not blinded to the purpose of the study, which may have influenced their responses to the survey.…”
Section: Limitations and Future Directionsmentioning
confidence: 98%